2014
DOI: 10.1007/s10584-014-1262-5
|View full text |Cite|
|
Sign up to set email alerts
|

A wedge-based approach to estimating health co-benefits of climate change mitigation activities in the United States

Abstract: A wedge-based approach to estimating health co-benefits of climate change mitigation activities in the United States

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(8 citation statements)
references
References 8 publications
1
7
0
Order By: Relevance
“…Our estimated health‐related costs are broadly consistent with other studies investigating different aspects of the national economic impacts of climate‐sensitive events (Balbus et al, ; Martinich & Crimmins, ). The health‐related costs estimated here are of similar magnitude as the $14.1 billion estimated in the prior analysis encompassing six events from 2000 to 2009, though differing geographies and time horizons preclude a direct cost comparison (Knowlton et al, ).…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Our estimated health‐related costs are broadly consistent with other studies investigating different aspects of the national economic impacts of climate‐sensitive events (Balbus et al, ; Martinich & Crimmins, ). The health‐related costs estimated here are of similar magnitude as the $14.1 billion estimated in the prior analysis encompassing six events from 2000 to 2009, though differing geographies and time horizons preclude a direct cost comparison (Knowlton et al, ).…”
Section: Discussionsupporting
confidence: 89%
“…Global Change Research Program, 2018). The evidence base for national climate-sensitive health-related costs is growing (Balbus et al, 2014;Martinich & Crimmins, 2019;U.S. Global Change Research Program, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Some studies have shown that even a small increase in air pollutants would lead to increased health costs. For example, the study of Balbus et al [36] on the transportation, construction and power sector in the US revealed that reducing PM 2.5 emissions by 2020 would reduce healthcare costs from US $6 billion to US $3 billion. Other studies had similar results.…”
Section: Literature Reviewmentioning
confidence: 99%
“…There are only a few studies that evaluate the health co-benefits in monetary terms arising from the reductions in GHGs. Examples of such studies include the cement industry [ 15 ], the power or energy sector [ 16 , 17 ], fuel switching households [ 18 ], and the transportation and energy sectors [ 19 , 20 ]. Some studies evaluate the health co-benefits for the emission reductions of GHGs for a whole country, sub-national regions, or regions in general, and include South Korea [ 21 ], Mexico [ 22 ], the north-western region of the US [ 23 ], California [ 24 ], Sweden [ 25 ], China [ 26 ], and Europe [ 27 , 28 ].…”
Section: Introductionmentioning
confidence: 99%